Pengaruh Air Payau Terhadap Kuat Tekan Beton dengan Semen PCC - Nugraha, Aditya Wisnu; Niken, Chatarina; Wahono, Endro Prasetyo; Isneini, Mohd. (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2023)
AbstractConcrete is a type of construction that is widely used today, one of which is water building infrastructure. Concrete must be resistant to various environmental conditions, such as brackish water. Brackish water is an aggressive environment with chemical contents that can interfere with the compressive strength of concrete. Currently, PCC type cement (Portland Composite Cement) tends to be more widely used than OPC (Ordinary Portland Cement) because the price is cheaper and more environmentally friendly, which has an impact on global warming. The aim of this research is to determine the impact of the aggressive environment of brackish water on the compressive strength of concrete with PCC cement. 18 cylindrical test objects with a diameter of 15 cm and a height of 30 cm were used, which were divided into two types of tests, namely protected concrete and concrete submerged in brackish water. Each test is carried out with three test objects at concrete ages of 28 days, 56 days, and 90 days. The data obtained was then analyzed using the Dixon criteria in accordance with ASTM E 178-02. Compressive strength testing is obtained from the Compression Testing Machine (CTM). The research results show that brackish water has a negative impact on the compressive strength of concrete. At the age of 28 days, the concrete submerged in brackish water reaches its design compressive strength. However, at 56 days and 90 days, the concrete experienced a decrease in compressive strength compared to protected concrete. This is because there is chloride and sulfate content in brackish water, which can damage the structure in the concrete.Keywords : brackish water, compressive strength, concrete, PCC. AbstrakBeton merupakan jenis konstruksi yang banyak digunakan saat ini salah satunya tiang pancang pada dermaga. Beton harus tahan terhadap berbagai kondisi lingkungan seperti air payau. Air payau adalah lingkungan agresif dengan kandungan kimia yang dapat mengganggu kuat tekan beton. Saat ini, semen jenis PCC (Portland Composite Cement) cenderung lebih banyak digunakan dibanding OPC (Ordinary Portland Cement) karena harganya yang lebih murah dan lebih ramah lingkungan karena pemanasan global. Tujuan penelitian ini adalah mengetahui dampak lingkungan agresif air payau terhadap kuat tekan beton dengan semen PCC. Digunakan 18 buah benda uji silinder dengan ukuran diameter 15 cm dan tinggi 30 cm yang terbagi menjadi dua jenis pengujian yaitu beton terlindung dan beton terendam air payau. Dimana setiap pengujian dilakukan dengan 3 buah benda uji pada umur beton 28 hari, 56 hari dan 90 hari. Dari data yang diperoleh kemudian dianalisis dengan kriteria dixon sesuai dengan ASTM E 178-02. Pengujian kuat tekan didapat dari alat Compression Testing Machine (CTM). Hasil penelitian menunjukkan bahwa air payau berdampak negatif terhadap kuat tekan beton. Pada umur 28 hari, beton terendam air payau mencapai kuat tekan rencananya. Namun, pada umur 56 hari dan 90 hari beton mengalami penurunan kuat tekan jika dibanding dengan beton terlindung. Hal ini dikarenakan terdapat kandungan klorida dan sulfat pada air payau yang dapat merusak struktur didalam beton.Kata kunci : air payau, beton, kuat tekan, PCC.